The Relationship Between The Level of Parental Education With Parenting Children Aged 3-4 Years in Early Childhood MTA Gondangjagir - Musta’in; Dwi Lestari Palupi; Danisa Nur Putri Aydi (Proceeding of International Conference on Science, Health, And Technology, 2019)
The pattern of parenting given to their children if it is not right can hinder the child's development and intelligence. This study aims to determine the relationship of parents 'level of education with parenting 3 - 4 years old children in early childhood MTA Gondangjagir, Ngadirejo Village, Mojogedang District, Karanganyar Regency in 2016. This study aims to determine the relationship of parents' level of education (father) with parenting 3 - 4 years old children in early childhood MTA Gondangjagir, Ngadirejo Village, Mojogedang District, Karanganyar Regency. The research method uses inferential analytical observational, hypothesis with cross sectional design. Sampling with Total Sampling techniques. The sample used was 55 respondents. Results: Parenting applied by parents to the majority democratic children, namely 45 respondents (81.84%). There is no significant relationship between the level of education of parents (fathers) with parenting of children aged 3-4 years as evidenced by the results of the Chi-Squere test with α = 0.05 Asymp obtained. Sig. = 0.947. This shows that the value of p> 0.05 means that there is no positive relationship of 0.947 or 94.7%.